Methodological Conditions for Learning Biology Through Writing and Arguing: University Students' Perspectives - Molina, Maria Elena (2016)
During recent years, research has tried to establish the role that argumentation and writing play in learning different disciplines. This attempt has been particularly relevant in the field of Science Education. Therefore, this work presents preliminary results of a research aimed to identify and characterize the didactic conditions for learning Biology by means of arguing and writing at university. This research has been carried out since 2012 in an introductory Biology course belonging to the "Ciclo Básico Común" of the University of Buenos Aires. Focusing on the analysis of interviews, we try to establish how students in one Biology course perceive the activities of argumentation and writing proposed by their professors. In this regard, we find that, in this class, students appreciate five didactic conditions under which writing and arguing would function as epistemic tools for learning Biology. In this vein, the systematic work with writing and arguing help students think differently about the subject and, consequently, this allows them to participate and use the disciplinary concepts in practical matters and real life situations.